2022
DOI: 10.1016/j.dialog.2022.100005
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon Haiyan survivors at the resettlement sites: Covid-19 pandemic realities and challenges

Abstract: More than 15 thousand households have been relocated in Tacloban North, Philippines, after typhoon Haiyan devastated the city in November 2013. While still recovering from the longer-term impacts of the typhoon, these households are currently enduring the impacts of the Covid-19 pandemic. This paper reports the contemporary realities and challenges Haiyan survivors face at the resettlement sites based on the inputs of 19 key informants we interviewed from September to November 2020. Our data reveal that the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In addition, little is known about the status quo and related factors of university students' attitude towards COVID‐19 vaccine uptake in the epicentre areas of China. While Sichuan Province is located in the earthquake epicentre in China, with the earthquake incidence ranking among the top three in China all the year round (China Earthquake Administration [CEA], 2021 ), and studies have shown that the occurrence of natural disasters increases the difficulty of pandemic prevention and control (Mangada & Cuaton, 2022 ; Mavroulis et al, 2021 ). In summary, only with high rates of acceptance and coverage can the campus immunization program succeed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, little is known about the status quo and related factors of university students' attitude towards COVID‐19 vaccine uptake in the epicentre areas of China. While Sichuan Province is located in the earthquake epicentre in China, with the earthquake incidence ranking among the top three in China all the year round (China Earthquake Administration [CEA], 2021 ), and studies have shown that the occurrence of natural disasters increases the difficulty of pandemic prevention and control (Mangada & Cuaton, 2022 ; Mavroulis et al, 2021 ). In summary, only with high rates of acceptance and coverage can the campus immunization program succeed.…”
Section: Introductionmentioning
confidence: 99%